Predictive models to determine the behavior of plastic and liquid limit of Lateratic soil for Raod construction at Egbema: Imo state of Nigeria - Eluozo, Solomon Ndubuisi; Nwaobakata, C. (International Journal of Engineering and Technology, 2012)
Predictive values to determine the behaviour of plastic and liquid of lateritic soil for road design and construction has been developed,  this two parameters has a relationship in term of soil classification through their laboratory results, both parameters sample were subjected to through laboratory analysis for  several locations, the laboratory results of both parameters were plotted to determine there behavious and limits, the results generated equations  at various locations, the equations were resolved and it generated theoretical values, the model values displayed there relationship on the classification of soil for road construction. The implementation of a laboratory testing proceedure is to classify subgrade material and assess sustain properties and moisture sensitivity (heavy, collapse, softening) that can influence long-term pavement performance. Testing implementation   consists of classification testing, these are (i.e., gradation analysis, Atterberg Limits and sulfate tests). Generated predictive models producing theoretical values,  are  engineering properties of soil  testing for  various parameters (i.e., swell/consolidation, R-value, unconfined compressive strength, California Bearing Ratio, and Resilient Modulus Tests). This are also design parameters that should generate predictive models that can be applied as design parameter in the study area, the study is imperative because predictive models generated and validated has ascertain proof of the workability of the models as design parameter in design of flexible pavements in the study location.